2020
DOI: 10.1002/pd.5653
|View full text |Cite
|
Sign up to set email alerts
|

Rapid prenatal diagnosis of skeletal dysplasia using medical trio exome sequencing: Benefit for prenatal counseling and pregnancy management

Abstract: Objective: The aim of this study is to explore the utility of rapid medical trio exome sequencing (ES) for prenatal diagnosis using the skeletal dysplasia as an exemplar.Method: Pregnant women who were referred for genetic testing because of ultrasound detection of fetal abnormalities suggestive of a skeletal dysplasia were identified prospectively. Fetal samples (amniocytes or cord blood), along with parental blood, were send for rapid copy number variations testing and medical trio ES in parallel.Results: De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 25 publications
(23 reference statements)
6
38
2
Order By: Relevance
“…As many single-gene disorders can present in-utero, it was postulated that exome sequencing could provide additional diagnosis, owing to its greater resolution and demonstrated utility in diagnosing postnatal cases such as developmental disorders [1]. Initial studies focused on highly selected and phenotypically homogenous cohorts which showed high diagnostic yield, up to 80% for select phenotypes such as skeletal anomalies [2][3][4][5]. When broader inclusion criteria are applied, diagnosis is made in ~10% [6,7].…”
Section: Accepted Articlementioning
confidence: 99%
“…As many single-gene disorders can present in-utero, it was postulated that exome sequencing could provide additional diagnosis, owing to its greater resolution and demonstrated utility in diagnosing postnatal cases such as developmental disorders [1]. Initial studies focused on highly selected and phenotypically homogenous cohorts which showed high diagnostic yield, up to 80% for select phenotypes such as skeletal anomalies [2][3][4][5]. When broader inclusion criteria are applied, diagnosis is made in ~10% [6,7].…”
Section: Accepted Articlementioning
confidence: 99%
“…Thirty-one studies published prenatal analysis by WES with the diagnostic rates between 6.2% and 80% [4]. Notably, the application of targeted exome sequencing in prenatal diagnosis of skeletal dysplasia is outstanding as several researches have reported high detection rates from 75% to 83.3% [5][6][7][8]. De nitive molecular diagnosis can provide accurate results instead of a suspected clinical impression and information about subsequent development of the disease and treatmentregimens, thus parents get consultation and birth defect intervention could be implemented.…”
Section: Introductionmentioning
confidence: 99%
“…Over 400 different conditions with arthrogryposis multiplex congenita have been identified and over 320 genes are involved (Hall & Kiefer, 2016; Han et al, 2020); however, the most severe neonatal lethal form is rare and only a minority of affected cases currently obtains a definite genetic diagnosis (Han et al, 2020; Niles, Blaser, Patrick Shannon, & Chitayat, 2019; Todd et al, 2015). We speculate that the AMC phenotype in this fetus occurs due to the loss of brain neurons seen in the mouse embryos and looks more severe than the previously reported KIDINS220 cases based on the early gestational age at the diagnosis of joint contractures and the associated hydrops fetalis.…”
Section: Discussionmentioning
confidence: 99%